2010
DOI: 10.1007/s11368-010-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil soluble organic carbon and nitrogen pools under mono- and mixed species forest ecosystems in subtropical China

Abstract: Purpose The objective of the present study was to assess the differences in soil total C and N, microbial biomass C and N, soil soluble organic C and N among eight monoand mixed species forest ecosystems (18-year-old restoration) in subtropical China. Materials and methods Soil samples were taken at the 0-10 and 10-20-cm depths from each of the eight forest ecosystems: Masson pine (CP1); Pitch pine (CP2); mixed Slash pine and Sweetgum (CBMP1); mixed Slash pine and Camphortree (CBMP2); mixed Masson pine, Sweetg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 38 publications
3
16
0
1
Order By: Relevance
“…This suggested that soils under broadleaf forest plantations were less stressful and in the better status for restoration of the productivity and function of the eroded red soil. It was in accordance with the result that the broadleaf forest ecosystems could be a better choice for the restoration of L-(+)-Arabinose red soil chemical and biological prosperities than the conifer-broadleaf forest ecosystems and coniferous forest ecosystems (Jiang et al 2010a).…”
Section: Metabolic Diversity Of Soil Bacteriasupporting
confidence: 89%
See 1 more Smart Citation
“…This suggested that soils under broadleaf forest plantations were less stressful and in the better status for restoration of the productivity and function of the eroded red soil. It was in accordance with the result that the broadleaf forest ecosystems could be a better choice for the restoration of L-(+)-Arabinose red soil chemical and biological prosperities than the conifer-broadleaf forest ecosystems and coniferous forest ecosystems (Jiang et al 2010a).…”
Section: Metabolic Diversity Of Soil Bacteriasupporting
confidence: 89%
“…This confirms the role of the C substrate quality in determining C utilization (Paul and Clark 1989). This is explained that, at the same experimental sites, soil soluble C and N pools extracted by both hot water and KCl solution and the MBC and MBN were the greatest under the broadleaf forest ecosystems, followed by the mixed conifer-broadleaf forest ecosystems, and then the conifer forest ecosystems (Jiang et al 2010a). …”
Section: Metabolic Diversity Of Soil Bacteriamentioning
confidence: 82%
“…The elevation of SWC increased bacterial biomass [51] while weakening fungal biomass [20]. Needles decompose slowly, leading to a thicker humus layers under conifer vegetation than broadleaf, which may have been a barrier to precipitation into soil and eventually lowered SWC in topsoil under conifer [52,53].…”
Section: The Relationships Of Vegetation Types Soil Properties and mentioning
confidence: 99%
“…Relative small changes in the sizes and distribution of soil C and N pools may therefore induce substantial effects on atmospheric greenhouse gas concentrations and on global C and N cycling at large (Belay-Tedla et al 2009;Xu and Chen 2006). Such alterations in labile and less labile C and N pools may not only lead to new dynamic processes in the short term but can also influence the long-term terrestrial C and N storage and consequently feedback to the atmosphere Burton et al 2010;Jiang et al 2010;Xing et al 2010). Studies have also demonstrated that labile C and N pools in some situations could be sensitive to alterations in soil moisture, temperature and plant community structure resulting from climate change (Zak et al 1993;Xu et al 2009).…”
Section: Introductionmentioning
confidence: 99%